Spectrophotometric Methods for Simultaneous Estimation of Hydrochlorthiazide and Valsartan - S. Chitlange, Sohan; A. Agarwal, Babita; B. Wankhede, Sagar; M. Sakarkar, Dinesh (Asian Journal of Chemistry, 2010)
Two simple, rapid, accurate and precise spectrophotometric methods have been developed for simultaneous estimation of hydrochlorthi-azide and valsartan from tablet dosage form. Method I involves, formation of Q-absorbance equation at 264 nm (isoabsorptive point) and 270.5 (λmax of hydrochlorthiazide); while method II multicomponent mode of analysis involves the measurement of absorbances at two wavelengths 270.5 (λmax of hydrochlorthiazide) and 248.5 (λmax of valsartan) in methanol. The linearity lies between 2-30 μg/mL for hydrochlorthiazide and 2-80 μg/mL for valsartan, respectively. The accuracy and precision of the method was determined and validated statistically. The method showed good reproducibility and recovery with RSD % less than 1. The method was found to be rapid, economical, specific, precise and accurate and can be successfully applied for the routine analysis of hydrochlorthiazide and valsartan in bulk and combined dosage form.